From preservation to sharing: photography and the design of new museum practices at the Théo Brandão Museum of Anthropology and Folklore (Cadernos de Sociomuseologia, 2020)
This research discusses restitution practices in museum institutions based on the work of sharing a set of photographs from the collection of the Théo Brandão Museum of Anthropology and Folklore (MTB) of Federal University of Alagoas. We select the “Guerreiro” subseries, a document of the most emblematic play in the state of Alagoas. While these photographs are products of meaning in a specific intellectual context, the regional movements and policies for the defense and promotion of folklore, it is also known that the classificatory and informative framework in museum objects is always transitory and procedural. As interviews with masters and coordinators of Guerreiros’ groups active in Maceió expand the possibilities of interpretations of this collection, they point out issues such as living conditions, migrations, gender roles and authorship, while also providing opportunities for reflections that lead to the design of new museum practices.Key-words: Photographic collection; Guerreiro; Alagoas